Current Trends in Tolerance Induction in Cow's Milk Allergy: From Passive to Proactive Strategies - Sackesen, Cansin; Altintas, Derya Ufuk; Bingol, Aysen; Bingol, Gulbin; Buyuktiryaki, Betul; Demir, Esen; Kansu, Aydan; Kuloglu, Zarife; Tamay, Zeynep; Sekerel, Bulent Enis (Frontiers in Pediatrics, 2019)
This review addresses the current strategies of inducing tolerance development in infant and childhood cow’s milk protein allergy (CMPA). The change in prevention strategies for CMPA has been emphasized based on the lack of evidence to support the efficacy of food allergen avoidance in infancy and the concept of the dual-allergen-exposure hypothesis, which suggests that allergen exposure through the skin leads to sensitization, whereas early oral consumption of allergenic food protein induces oral tolerance. The new approach is based on the likelihood of early introduction of allergenic foods to the infant’s diet to reduce the development of food allergies through oral tolerance induction. The latest treatment guidelines recommend the continuation of breast feeding and the elimination of cow’s milk and products from the maternal diet in exclusively breast-fed infants with CMPA, the use of an extensively hydrolyzed infant formula (eHF) with proven efficacy in CMPA as the first elimination diet in formula-fed infants with CMPA and the use of amino acid-based formula (AAF) in severe cases, such as anaphylaxis, enteropathy, eosinophilic esophagitis and food protein-induced enterocolitis syndrome (FPIES), as well as cases of multiple system involvement, multiple food allergies and intolerance to extensively hydrolyzed formula (eHF). In conclusion, this paper presents the current knowledge on tolerance development in infants and children with CMPA to increase the awareness of the clinicians concerning the new approaches in CMPA treatment Tolerance development is considered a relatively new concept in CMPA, inducing a shift in interventions in CMPA from a passive (avoidance of responsible allergen) towards a proactive (tolerance induction) strategy.